Determinantes das exportações de frutas da Região Nordeste brasileira (2000-2018): uma análise sob a ótica do modelo gravitacional - Lisbinski, Fernanda Cigainski (2021)
This work aimed to analyze the export performance of the main fruits produced in northeastern Brazil, lemons and limes, melon, mango, grape, and cashew nuts, for their main markets of destination, taking as reference the period from 2000 to 2018. For this purpose, the Gravitational Model and the Comparative Advantage Index Revealed were used as a methodology, verifying whether the Northeast region has a comparative advantage in fruit production in the regional and international scenarios. The main results showed that melon, cashew nut, and mango showed comparative advantage revealed in the international market throughout the analyzed period, while the grape showed loss of revealed comparative advantage and lemons and limes comparative advantage gain revealed over time. The estimated gravity model was presented in a pooled format, Fixed Effect, and Random Effect and Corrected Random Effect (White's Robust Estimator) and Generalized Least Square (GLS) due to the presence of heteroscedasticity and autocorrelation of the models, enabling eventual correlations. It is demeaned that the parameter used for the interpretation of the results was the GLS model, considering that, according to the literature, it is preferred and most appropriate in the presence of autocorrelation and heteroscedasticity. The estimates of the severity models presented results consistent with seminal studies of the economic literature, which indicate that trade flows are positively related to the incomes of importing countries and negatively with the distance between importing and exporting countries. Moreover, it was possible to observe that the export performance of each fruit analyzed has its own characteristics, so that the impact of the analyzed variables affects this performance differently, highlighting the importance of this desegregated analysis.